2022
DOI: 10.1002/alz.060983
|View full text |Cite
|
Sign up to set email alerts
|

Mild behavioral impairment is associated with plasma p‐tau181 in a dementia‐free population

Abstract: BackgroundMild behavioral impairment (MBI) is a validated neurobehavioral syndrome describing emergent and persistent neuropsychiatric symptoms (NPS) as an at‐risk state for incident cognitive decline and dementia. In cognitively normal older adults MBI is associated with positron emission tomography and cerebrospinal fluid measured amyloid‐β and tau, the characteristic hallmarks of Alzheimer’s disease (AD). Plasma p‐tau181 is a blood‐based biomarker recently identified as an accessible alternative for in‐vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In older adults with MCI, only MBI was associated with a lower likelihood of reversion to normal cognition, whereas non‐MBI NPS showed no difference compared to no NPS 18 . This finding suggests that distinguishing MBI from non‐MBI NPS, the latter of which is often captured by the NPI and its derivatives, is essential to fully understand and make use of MBI as a tool for neurodegenerative disease research and for sample enrichment 4 . One issue with using the NPI and its derivatives for MBI is the reference timeframe by which the instruments assess NPS, which spans 1 month 29–31 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In older adults with MCI, only MBI was associated with a lower likelihood of reversion to normal cognition, whereas non‐MBI NPS showed no difference compared to no NPS 18 . This finding suggests that distinguishing MBI from non‐MBI NPS, the latter of which is often captured by the NPI and its derivatives, is essential to fully understand and make use of MBI as a tool for neurodegenerative disease research and for sample enrichment 4 . One issue with using the NPI and its derivatives for MBI is the reference timeframe by which the instruments assess NPS, which spans 1 month 29–31 .…”
Section: Introductionmentioning
confidence: 97%
“…MBI should be thought of as a subset of NPS that meet the aforementioned criteria (Figure S1), which improve specificity for the NPS identified by MBI representing early‐stage neurodegenerative disease as a complementary behavioral analog to late‐life emergent cognitive symptoms 2 . As such, MBI can improve early dementia risk detection, thereby facilitating research into early neurodegenerative disease mechanisms and the development of preventative or disease‐modifying treatments 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As such, MBI has the potential to improve early detection of dementia risk, thereby facilitating research into early neurodegenerative disease mechanisms and the development of preventative or disease-modifying treatments. 3,4 The Mild Behavioral Impairment Checklist (MBI-C) was developed specifically to capture NPS that meet the criteria for MBI. 5 Studies that used the MBI-C demonstrated poorer cognition and greater β-amyloid (Aβ) and tau pathology, medial temporal lobe atrophy, and Alzheimer's disease (AD) genetic risk in older adults with MBI.…”
Section: Introductionmentioning
confidence: 99%
“…19 This finding suggests that distinguishing MBI from non-MBI NPS is essential to fully understand and make use of MBI as a tool for neurodegenerative disease research and for sample enrichment. 4 One issue with using the NPI and its derivatives for MBI is the reference timeframe by which the instruments assess NPS, which spans one month. [28][29][30] In contrast, the MBI-C reference frame is six months, consistent with the symptom persistence criterion for MBI.…”
Section: Introductionmentioning
confidence: 99%